PEDAGOGICAL RESOURCES IN STORYTELLING FOR AUTISTIC CHILDREN IN EARLY CHILDHOOD EDUCATION - Ferreira, Jussara Machado; Pereira, Cléia Demétrio; Desdewalle, Shayan (Seven Editora, 2025)
This article presents the preliminary results of an ongoing research within the scope of the Graduate Program of the Professional Master’s Degree in Inclusive Education. The study aims to investigate the influence of the use of pedagogical resources in storytelling as a strategy to promote the development of skills in autistic children in early childhood education, with emphasis on orality, reading, writing and social interaction. The research seeks to identify the most recurrent pedagogical resources in storytelling for autistic children, taking into account their specific needs and characteristics, and to analyze how this practice can favor understanding and interactions in the educational environment. The problem that guides the study is: how can pedagogical resources be used in storytelling to contribute to the learning of autistic children in early childhood education? The methodological approach is qualitative, exploratory and bibliographic (Gil, 2008), with thematic analysis by Bardin (2011). The research involved a survey in databases such as the Digital Library of Theses and Dissertations and the Portal of the Coordination for the Improvement of Higher Education Personnel, in the period from 2013 to 2023. The results show the scarcity of scientific production on the subject, but highlight authors such as Silva (2022), Lima (2018), Queiroz (2017) and Battistello et al. (2020), who reinforce the importance of storytelling with pedagogical resources as an inclusive strategy that enhances child development. DOI: https://doi.org/10.56238/sevened2024.037-200